The Role of Foreign Loans in the Implementation of the Precautionary Principle - Johan, Suwinto (Jurnal Riset Pendidikan Ekonomi, 2024)
Every country requires financing for its development from both domestic and foreign sources. Many countries take on foreign loans to offset their development financing deficits. However, these foreign loans carry a default risk, necessitating prudent management. This research was performed to evaluate the contributions and management of foreign loans based on the principle of prudence using a normative method. This research regarded primary data, secondary data, and other forms of data to arrive at conclusions. The results showed that foreign loans primarily serve to cover a country's development balance deficit and must be managed with caution. One practical measure is requiring recipients of foreign loans to have their debt independently rated by a rating agency. Moreover, the usage of foreign debt should be critically assessed to ensure it fosters economic growth, and authorities should avoid deploying these funds for consumer purposes.